Peran Pengelolaan Manajemen Terhadap Kinerja Koperasi Syariah Bmt Sri Deli Dalam Membantu Usaha Kecil Di Lingkungan Stais Tebingtinggi Deli: Peran Pengelolaan Manajemen Terhadap Kinerja Koperasi Syariah - Herry Syahbannuddin Nst (STAI Tebing Tinggi Deli, 2019)
The fundamental problems faced by the small business trade sector in Indonesia are the lackof access to capital sources and the weak role of financial institution services. The expectedmicrofinance institutions tend to be more dominant in consumer financing than productivefinancing. While Islamic microfinance institutions have not yet played an optimal role. It isnot yet known how the contribution of sharia operations management in the development ofcooperative performance and its effect in increasing the distribution of productive financingto empower the small business trade sector